Pathologic findings of renal biopsies in children; an 11-year experience from a single center in West of Iran - Hossein Emad Momtaz; Arash Dehghan; Amir Fazeli (Society of Diabetic Nephropathy Prevention, 2022)
Background: Renal biopsy is an important diagnostic procedure in pediatric nephrology. Although considered as an invasive method, numerous renal diseases cannot be definitively diagnosed and treated without it. Objectives: The aim of this study was histopathological study of renal biopsy results in children of 6 months to 18 years old. Patients and Methods: In this retrospective cross-sectional study, the available data from children who had undergone kidney biopsy between 2007 and the end of 2017 were evaluated. Demographic data, indications of biopsy, the outcome of patients, biopsy complications and histopathologic findings were collected using a checklist. Finally, data were presented as frequency and percentages. Results: The most common cause of biopsy in children was nephrotic syndrome (43.7%). Focal segmental glomerulosclerosis (FSGS) with 39 cases (32.7%) had the highest frequency in examined biopsies. In the long-term follow-up, 71 children (59.7%) cured, 7 (5.9%) died, 25 (21.0%) continued treatment, 6 (5.0%) underwent a kidney transplant surgery, and the outcome of 10 children (8.8%) was unknown. While 6.7% of patients were diagnosed with complications of biopsy, the most frequent of them was hematuria. There was no case of death or nephrectomy and only one patient needed packed RBC transfusion. Conclusion: Nephrotic syndrome was the most common indication for kidney biopsy. FSGS had the highest frequency in examined biopsies.